Variation in the repulsive guidance molecule family in human populations. Issue 3 (11th February 2019) - Rotwein, Peter
Abstract: Repulsive guidance molecules, RGMA, RGMB, and RGMC, are related proteins discovered independently through different experimental paradigms. They are encoded by single copy genes in mammalian and other vertebrate genomes, and are ~50% identical in amino acid sequence. The importance of RGM actions in human physiology has not been realized, as most research has focused on non‐human models, although mutations in RGMC are the cause of the severe iron storage disorder, juvenile hemochromatosis. Here I show that repositories of human genomic and population genetic data can be used as starting points for discovery and for developing new testable hypotheses about each of these paralogs in human biology and disease susceptibility. Information was extracted, aggregated, and analyzed from the Ensembl and UCSC Genome Browsers, the Exome Aggregation Consortium, the Genotype‐Tissue Expression project portal, the cBio portal for Cancer Genomics, and the National Cancer Institute Genomic Data Commons data site. Results identify extensive variation in gene expression patterns, substantial alternative RNA splicing, and possible missense alterations and other modifications in the coding regions of each of the three genes, with many putative mutations being detected in individuals with different types of cancers. Moreover, selected amino acid substitutions are highly prevalent in the world population, with minor allele frequencies of up to 37% for RGMA and up to 8% for RGMB. These results indicate that protein sequence variation is common in the human RGM family, and raises the possibility that individual variants will have a significant population impact on human physiology and/or disease predisposition. Abstract : There is extensive variation in gene expression patterns, substantial alternative RNA splicing, and possible mis‐sense alterations and other modifications in the coding regions of each of the three human repulsive guidance molecule (RGM) genes, with many putative mutations being detected in individuals with different types of cancers. Selected amino acid substitutions are highly prevalent in the world population, with minor allele frequencies of up to 37% for RGMA and up to 8% for RGMB. It thus appears that protein sequence variation is common in the human RGM family, and raises the possibility that individual variants will have a significant population impact on human physiology and/or disease predisposition.